7 Dof Industrial Robot Controlled by Hand Gestures Using Microsoft Kinect v2 - Kern-Molina, J (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a control of a 7 degrees of freedom (7DOF) industrial robot using computer vision through Kinect v2. This project aims to facilitate the industrial process, improve safety, and include people with physical disabilities to control industrial robots by gestures recognition, using only the hands. © 2017 IEEE.